Deep Learning-Based Intelligent Recommendation System and Management for Personalized Islamic Religious Education Materials - Fauzi Iqbal Amali; Nur Aisyah (Al-Qalam Institue, 2026)
The purpose of this study is to examine the strategic role of information professionals in supporting digital transformation within educational institutions. Using a qualitative research design supported by a comprehensive literature review, this study analyzes how information professionals contribute to the planning, implementation, and sustainability of digital initiatives. The results reveal several major barriers to digital transformation, including limited budgets, resistance to change, inadequate skills, and insufficient technological infrastructure. Despite these challenges, information professionals serve as key change agents who promote innovation, improve administrative efficiency, and ensure stronger alignment between digital systems and institutional objectives. The findings imply that developing professional competencies, increasing digital literacy among stakeholders, and strengthening collaboration between information personnel and institutional leaders are essential for achieving sustainable digital transformation. This research contributes to a deeper understanding of human resource readiness for digital initiatives and offers practical insights for policymakers and educational leaders.